PENERAPAN DATA MINING DALAM PEMILIHAN LAPTOP MENGGUNAKAN METODE ALGORITMA C4.5 - sari, anggi wijaya; Sitohang, Sunarsan (LPPM Universitas Putera Batam, 2021)
The development of globalization today greatly affects various fields, one of which is technology. A laptop or handheld computer is a computer that can be carried anywhere because it has a small size and light weight. The use of a laptop is the same as a computer. Good Cell Batam store is one of the stores that provide various types of laptops. Because many types of laptops make it difficult for consumers to choose the right laptop so that the store has difficulty providing information to consumers. Then we need data mining techniques and C4.5 algorithm methods in classifying the right laptop selection based on price variables, RAM capacity, processor, size and battery life. The WEKA application is used to test the accuracy of the data processed using the C4.5 algorithm. These results are obtained by finding the entropy and gain values ​​of all variables so as to produce a decision tree where there are three variables that greatly affect the choice of laptop, namely price, processor and battery life from a total of 80 data where there are 53 choices of the right laptop and 27 choices of the right laptop. not exactly.